Control of Eragrostis plana Nees (capin-annoni) germination: innovation with botanical bioproducts (Research, Society and Development, 2022)
Eragrostis plana (capin-annoni) is an exotic grass brought to Brazil in 1950. Considered an invasive plant in several countries, it currently occupies approximately 10% of Pampa‘s Biome territory. The natural ecosystems of Río Grande do Sul associated with the Pampa Biome have suffered from E. plana invasion due to the expansion of the agriculture and livestock management, which makes empty spaces available for their establishment. The objective of this study is to evaluate the efficiency of botanical bioproducts produced from two plants native to the Pampa and one exotic in the control of  E. plana seed germination in two different seasons. For this, different concentrations of nanoemulsions of Melaleuca alternifolia and Baccharis crispa, essential oil and hydrolate of Aloysia gratissima were used. The design was in a 4x3+1 factorial scheme, with 4 bioproducts (treatments) and 3 concentrations + control treatment, with four repetitions. Results enabled to calculate the percentage and germination speed index, followed by the Kruskal-Wallis test and Dun's post hoc test with p